A Demographic Analysis of the Impact of Property Tax Caps on Indiana School Districts - Marilyn A. Hirth; Christopher Lagoni (Educational Considerations, 2014)
In 2008, the Indiana legislature passed and the governor signed into law House Enrolled Act No. 1001, now referred to as Public Law 146-2008, which capped Indiana school districts’ ability to raise revenues from the local property tax without local voter approval.
Keywords: property tax; Indiana; demographic; assessment; variables; school districts; data; analysis; procedures